The effects of rent controls in Latin America. A century of regulations in Argentina - Jacobo, Alejandro D. (2020)
Fil: Jacobo, Alejandro D. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas. Instituto de Economía y Finanzas; Argentina.